Boosting investment in agriculture research in Africa: Building a case for increased investment in agricultural research in Africa - Stads, Gert-Jan; Nin-Pratt, Alejandro; Beintema, Nienke (African Union, 2022)
Agricultural research and development (R&D) investment is positively associated with high returns, but these returns take time—often decades—to develop. Consequently, the inherent lag from the inception of research to the adoption of new technologies calls for sustained and stable R&D funding. In 2016, Africa invested just 0.39 percent of its agricultural GDP (AgGDP) in agricultural R&D, down from 0.54 percent in 2000. Even though in absolute terms total R&D investment has increased since the turn of the millennium—after a period of stagnation—most of the funds have been directed toward research staff expansion, salary increases, and rehabilitation of derelict research infrastructure and equipment, rather than actual research programs. In fact, in a large number of African countries, the national government funds the salaries of researchers and support staff, but little else, leaving nonsalary-related expenses highly dependent on donors and other funding sources.